Optimization of single-source multi-products multi destination supply chain system. (2011)
"Optimal allocation of products to downstream locations is a major requirement for minimizing the distribution costs associated with supply chain systems. Unfortunately many supply chain managers rely on their intuition and feelings to make these allocation decisions. In this study a mathematical model was developed for minimizing the distribution cost in a multi-product 2-echleon supply chain system. The distribution system of a leading bottling plant in Nigeria was studied to understand the underlying supply chain system . Attempt was made to identify system parameters, variables, limitations, criteria so as to be able to define the distribution problem The interactions and flow of products in the system were identified and characterized as a 2 echelon supply chain system. Mathematical model of the system was developed. The problem model, a linear program formulation with three major constraints; demand, availability and company policy requirements was parameterised based on demand data product availability data, company policies and unit transportation costs to various downstream locations. The model was solved for a 12 product 8 destination case. It was observed that the model application produces 6% reduction in the distribution cost compared to the existing practice of the company. It is concluded that the model is effective to reduce or minimize distribution expenses for any multiproduct multiple destination system and fulfilling demand at various destinations. "